Anti-Amnestic Effect of Iridoids Fraction from Pentas Lanceolata Leaves against D-Galactose Induced Brain Aging in Rats - Azza F. Arafa (Journal of Global Pharma Technology, 2016)
In this work the anti-amenstic effect of the iridoids-rich fraction isolated from Pentas lanceolata (IFPL) leaves was investigated using D-galactose (D-gal) to artificially create aging in rats. Thirty-two rats were divided as follows: 1st group served as control; 2nd, 3rd and 4th rat groups were injected intraperitoneally with 100 mg/kg D-gal five days/ week for two months. The 2nd group was left untreated. While, 3rd and 4th groups were treated daily orally with IFPL (50 mg/kg b. wt.) and the reference drug donepezil (10 mg/kg b. wt.), respectively for one month. Behavioral tests, T-Maze and beam balance, showed deterioration in cognitive ability of aging rats. D-gal caused a remarkable decrease in oxidative biomarkers except lipid peroxides which revealed a significant increase. In addition, D-gal-treated rats showed a significant decrease in the levels of neurotransmitters, while, a significant increase in acetylcholineasterase (AChE) was recorded. Furthermore; caspase-3 levels were elevated in aged brains which were confirmed by immunohistochemical analysis. Histopathological alterations were observed in these rats. Treatment of these rats with IFPL exhibited improvement in behaviour, neurobehavioral changes, modulated oxidative stress as well as apoptotic markers which is confirmed by histopathological investigations.These findings provide scientific evidence that IFPL extract has antioxidant, anti-inflammatory, immunomodulatory, anti-apoptotic and anti-amnesic properties against D-gal induced brain aging.Keywords: D-galactose, Brain aging, Pentas lanceolata, Iridoid-rich fraction